Experiments on Integral and Local Crystallization Fouling Resistances in a Double-Pipe Heat Exchanger With Wire Matrix Inserts. Issue 1 (2nd January 2016) - Goedecke, Robert; Drögemüller, Peter; Augustin, Wolfgang; Scholl, Stephan
Abstract : Wire matrix inserts are used in different applications of tubular heat exchangers to improve tube side heat transfer. They have also been used to suppress fouling in crude oil refining services. In this paper it is investigated whether the changed hydrodynamic and thermal conditions when applying wire matrix inserts have an impact on crystallization fouling compared to the plain tube. With a turbulent flow, at Reynolds number of 9877 and an inlet temperature of 42°C, fouling tests with an aqueous calcium sulfate solution for two wire matrix inserts with a different packing density were carried out and compared with a plain tube. Integral and local measurements of the fouling were performed. The experiments were realized in a double-pipe heat exchanger with a pipe length of 2000 mm. The integral fouling resistances between the inserts and the plain tube showed no significant difference, whereas major differences of the local fouling resistances were observed. Compared to the plain tube, the inserts showed an increased heat transfer up to a maximum of 35% but also a significantly increased pressure drop. Fouling on the inserts themselves, which was observed optically, is the possible explanation for this behavior.